Indonesian and Malaysian consumer perspective toward COVID-19 vaccine products from China - Hartono, Sri; Sabri, Mohamad Fazli; Gumilang, Dendi Anggi; Wijekoon, Rusitha (Inderscience Publishers, 2024)
The current study aimed to analyse the impact of country of origin on brand trust, perceived quality, and brand image directly and examined the influence of product brand image and perceived quality on brand trust. COVID-19 vaccine products from China were selected as the research object, and the current study was carried out in both Indonesia and Malaysia. Data were collected from 320 respondents from Indonesia (160) and Malaysia (160) who had experience of COVID-19 vaccine products from China, and the analyses were carried out using Smart PLS-SEM. All five tested hypotheses were accepted and supported by the previous research. Based on the results, the country of origin of a product is the most important determinant of product utilisation suitability and is significantly determined by brand trust, brand image, and perceived quality. The results also showed that the benefits of the country of origin had a significant impact on consumer confidence in choosing a brand, especially in the use of the COVID-19 vaccine in the current pandemic era.